Adivinación y presagios en el Bajo Imperio Romano según Amiano Marcelino - Santos Yanguas, Narciso (Estudios Humanísticos. Historia, 2015)
En el s. IV d. C. los romanos encontraron en sus convicciones religiosas motivos para creer en la adivinación. Uno de los rasgos de la mentalidad pagana consistía en ver en los hechos naturales una constante intervención divina y una consecuencia de los mensajes enviados a los hombres para estimular la ejecución de sus proyectos. Adivinación y presagios no sólo no experimentan una decadencia durante dicha e¡centurina sino que Amiano Marcelino parece buscar en sus Res Gestae justificación a tales prácticas. ABSTRACT: In the 4th century A.D. the Romans found in their own religious convictions and in their own culture reasons to believe in the practices of the diviners. One of the main features in the pagan mentality is to be found in the natural events as the outcome of divine intervention and a consequence of the messages sent to men to stimulate the execution of projects. Divination and presages will not suffer a process of decay during the said century and Ammianus Marcellinus seems to be trying to find in his Res Gestae justification of the practices mentioned.